2012
DOI: 10.1007/s00125-012-2756-1
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing-driven discovery of coding polymorphisms associated with common metabolic phenotypes

Abstract: Aims/hypothesisHuman complex metabolic traits are in part regulated by genetic determinants. Here we applied exome sequencing to identify novel associations of coding polymorphisms at minor allele frequencies (MAFs) >1% with common metabolic phenotypes.MethodsThe study comprised three stages. We performed medium-depth (8×) whole exome sequencing in 1,000 cases with type 2 diabetes, BMI >27.5 kg/m2 and hypertension and in 1,000 controls (stage 1). We selected 16,192 polymorphisms nominally associated (p < 0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 31 publications
4
104
0
1
Order By: Relevance
“…One recent study of the MTNR1B locus encoding melatonin receptor 1B indicated that this locus may not only contain common variants with low effect sizes (ORs <1.4), but may also contain rare variants with considerably stronger associations with the risk of type 2 diabetes (OR 5.7, 95% CI 2.2, 14.8) for rare lossof-function variants of the receptor [63]. Sequencing of all genes in the genome (exome sequencing), as recently reported for a Danish case-control study [64], and whole-genome resequencing, as performed in the 1000 Genomes Project [65], will improve our understanding of the potential relevance of low-frequency (0.5-5%) and rare (<0.5%) variants in the development of type 2 diabetes [66]. It remains to be seen to what extent ongoing studies and analyses of other kinds of genetic variations such as copy number and structural variations will contribute to more precise risk assessment.…”
Section: Genetic Variantsmentioning
confidence: 80%
“…One recent study of the MTNR1B locus encoding melatonin receptor 1B indicated that this locus may not only contain common variants with low effect sizes (ORs <1.4), but may also contain rare variants with considerably stronger associations with the risk of type 2 diabetes (OR 5.7, 95% CI 2.2, 14.8) for rare lossof-function variants of the receptor [63]. Sequencing of all genes in the genome (exome sequencing), as recently reported for a Danish case-control study [64], and whole-genome resequencing, as performed in the 1000 Genomes Project [65], will improve our understanding of the potential relevance of low-frequency (0.5-5%) and rare (<0.5%) variants in the development of type 2 diabetes [66]. It remains to be seen to what extent ongoing studies and analyses of other kinds of genetic variations such as copy number and structural variations will contribute to more precise risk assessment.…”
Section: Genetic Variantsmentioning
confidence: 80%
“…In the past decade, GWAS in large, open populations such as Europeans and Asians have proven highly successful in identifying common variants associated with complex diseases and traits, among them T2D and related metabolic traits [15][16][17][18][19][20]. Developments in genotyping and sequencing technologies have further enabled the study of lowfrequency and rare genetic variation [18,21,22].…”
Section: Gwas In Population Isolatesmentioning
confidence: 99%
“…For five loci (SLC30A8, GCKR, PPARG, KCNJ11-ABCC8, PAM), the coding variants identified had previously been nominated as causal for their respective GWAS signals 2,7,13 . For the other seven loci, GWAS metaanalyses had previously highlighted a lead variant in non-coding sequence 2,5,6 .…”
Section: Analysis Of Coding Variationmentioning
confidence: 99%
“…However, the contribution to T2D risk attributable to lower-frequency variants remains a matter of considerable debate, not least because of the relevance of disease architecture to clinical application 11 . Next-generation sequencing enables direct evaluation of the role of lower-frequency variants to disease risk 7,12,13 . This paper describes the efforts of the coordinated, complementary strategies pursued by the Genetics of Type 2 Diabetes (GoT2D) and T2D-GENES (Type 2 Diabetes Genetic Exploration by Next-generation sequencing in multi-Ethnic Samples) Consortia.…”
mentioning
confidence: 99%